Candy Perfume Girl - Pausé, Cat (My University, 2017)
Fat bodies have long been used for the purposes of entertainment. But unlike their negative presentations in circuses and seaside attractions, members of the fat activist community are embracing ways to show positive representations of fatness and fat bodies; One of these ways is coloring books. Fat positive coloring books are exploring the ways in which fat activists use the medium to queer fatness and provide alternative visual representations of fat bodies. Works included Fat ladies in spaaaaaaaace by Theo Nicole Lorenz (2011), FATSPO coloring book by Brian Stuart (2013), Big-bellied Merbabes: A body positive coloring by Rachelle Bellar (2013), Body love: A fact activist coloring book by Allison Tunis (2016), Fat bodies coloring by Sarah Burns (2016),  The big fat little coloring zine by Natalie Perkins (2016), and Superfat crop top girl gang coloring book Zine by Rachele Cateyes (2016). Fat positive coloring books embrace subversive themes, queer fatness, and display positive representations of fat bodies and fatness.
Colouring in Fat Bodies
Keywords: 700 Künste, Bildende und angewandte Kunst; Fat Studies; Queering; Colouring; Books; Intersectionality